Cyclic-Imide-Hydrolyzing Activity of d-Hydantoinase from Blastobacter sp. Strain A17p-4 - Soong, Chee-Leong (American Society for Microbiology, 1999)
The cyclic-imide-hydrolyzing activity of a prokaryotic cyclic-ureide-hydrolyzing enzyme, d-hydantoinase, was investigated. The enzyme hydrolyzed cyclic imides with bulky substituents such as 2-methylsuccinimide, 2-phenylsuccinimide, phthalimide, and 3,4-pyridine dicarboximide to the corresponding half-amides. However, simple cyclic imides without substituents, which are substrates of imidase (i.e., succinimide, glutarimide, and sulfur-containing cyclic imides such as 2,4-thiazolidinedione and rhodanine), were not hydrolyzed. The combined catalytic actions of bacterial d-hydantoinase and imidase can cover the function of a single mammalian enzyme, dihydropyrimidinase. Prokaryotic d-hydantoinase also catalyzed the dehydrative cyclization of the half-amide phthalamidic acid to the corresponding cyclic imide, phthalimide. The reversible hydrolysis of cyclic imides shown by prokaryotic d-hydantoinase suggested that, in addition to pyrimidine metabolism, it may also function in cyclic-imide metabolism.